Securitization Theory Insights on the Formation of an EU Army - Iva Zutic; Robert Mikac (Journal of Liberty and International Affairs)
This paper analyzes the narrative securitized by Eurofederalists in support of establishing an EU army. The main objective is to identify and categorize the assertions employed by securitizing actors in their speech acts, examined through the framework of securitization theory. To assess the impact of this securitized narrative, the study evaluates its reception among the EU public before and after the outbreak of the war in Ukraine. The research reveals that securitizing actors cluster their assertions around four advantages: strategic, political, societal, and economic. Furthermore, the findings indicate that by framing these advantages within their narrative, securitizing actors have successfully influenced public opinion in the EU to favor the establishment of an EU army.